A finite element modelling study of strain localization in the vicinity of near-surface cavities as a cause of subsurface fatigue crack initiation - Mughrabi, Hael; Höppel, Heinz Werner; et al. (International Journal of Fracture, 2002)
Recently, several observations of subsurface fatigue crack initiation in the vicinity of cavities in cast and in powder metallurgical (PM) alloys have been reported. In an attempt to explain these rather unexpected observations, an FE (finite element) modelling study of the stress and strain fields around spherical cavities of radius r lying at different distances below the surface of a tensile-stressed material has been performed. The results show that, due to the local stress enhancement in the 'bridge' of material between the cavity and the surface, an increasingly severe strain localization develops, as the distance d between the centre of the cavity and the free surface decreases and as the ratio rl(r + d) approaches 0.5 for a cavity located just underneath the surface (r = d). It is concluded that, under conditions of cyclic stressing, the strain localization in the immediate near-surface vicinity of a cavity lying just beneath the surface can be severe enough to cause the initiation of subsurface fatigue cracks. Depending on the detailed situation, these fatigue cracks can be initiated at the pore or at the adjacent outer surface.
UnivIS-Import:2015-03-09:Pub.2002.tech.IW.LWAW.afinit
Keywords: (Cylic) strain localization; Cavities; Finite element (FE) modelling; Subsurface fatigue crack initiation